Validation of prisk tool for periodontal screening of patients with diabetes by non-dental practitioners / Wan Sophia Wan Ab Naim - Wan Sophia , Wan Ab Naim (2024)
Background and Objective: Studies have reported a bi-directional association between periodontal disease (PD) and diabetes mellitus (DM), highlighting the critical role of oral health in comprehensive DM care. The Periodontal Risk Assessment (PRISK) tool, comprising a self-reported questionnaire (Part A) and an intraoral assessment (Part B), was developed to be used for periodontal referrals by non-dental practitioners to the dental clinic. However, the PRISK tool has not been validated. Thus, this study aimed to validate the PRISK tool as a screening tool for PD among non-dental practitioners to improve the detection and timely management of PD among patients with DM in the University Malaya Medical Centre (UMMC). Methods: A cross-sectional study was utilized. Two additional questions were added to the PRISK tool. Content validity for these questions were done by a review of 4 experts and face validity by 10 patients with DM and 10 non-dental practitioners. Pilot tests were conducted on 30 patients with DM. Test-retest was conducted with 30 participants, where the same procedures were repeated after 2 hours. A validation study was conducted involving 128 patients with diabetes and 20 non-dental practitioners (endocrinologists and medical officers) from the Primary Care Clinic and Diabetes Specialist Clinic, UMMC. Each participant answered a self-reported questionnaire (Part A) and received an intraoral assessment (Part B) from non-dental practitioners. Reliability was determined by internal consistency and test-retest. The outcomes from the PRISK tool were validated against the Basic Periodontal Examination (BPE). Sensitivity, specificity, positive and negative predictive value analysis were subsequently conducted comparing these two tools. Results: The Content Validity Index (CVI) and Face Validity Index (FVI) demonstrated an excellent score of 1.0. The internal consistency reliability of the PRISK tool was 0.52. There was no significant difference between test-retest (p= 0.125). PRISK tool had a high sensitivity of 81.6% and a low specificity of 0%. The positive predictive value (PPV) was 97.1% and the negative predictive value (NPV) was 0%. Conclusion: Within the limitations of this study, the PRISK tool was found to be reliable and valid in screening PD among patients with DM. This can enhance and facilitate the referral process for periodontal care to dentists by non-dental practitioners. However, further modifications need to be done to improve the specificity and internal reliability of the PRISK tool in screening PD among patients with DM.